The Socio-Economic Impact of Diving Sports Tourism at the Ex-Sail Tomini Location, Tandaigi Village, Parigi Moutong Regency - Delfiero Delfiero; Bambang Budi Raharjo; Donny Wira Yudha Kusuma (STKIP Muhammadiyah Kuningan, 2023)
This study aims to examine the socio-economic impact of diving tourism at the former Sail Tomini location, Tandaigi Village, Parigi Moutong Regency. This study uses a mixed method with an ethnographic approach. The sampling technique in this study used a non-probability sampling method with a purposive sampling approach with sample characteristics that the researcher had determined as the primary data source based on the research objectives. The results of this study: 1). The Parigi Moutong government's promotional strategy through the Sail Tomini Festival, which in this activity displays the natural charm and cultural tourism of Parigi Moutong and is assisted by Instagram and Facebook social media, is a very effective promotional tool in attracting visitors, providing a forum for the community by forming tourism-aware community groups where aims to train and provide assistance to the community on how to manage, maintain cleanliness, maintain security to provide a comfortable and safe atmosphere for the community and also visitors. 2). Domination by providing services, such as Services to become a Diving Guide, Boat Steering and Ship crew, and resort manager. As for equipment rental, the community still needs to open a rental facility for diving equipment due to limited costs because diving is a sport with cheap equipment. 3). the existence of diving sports tourism in Tandaigi Village is in a Good category with a percentage level of 42%. With the second-highest percentage in the less category with a total rate of 28%, the suitable type is in third place with a full share of 27%, while the class gets a percentage of 3% and significantly less gets a real rate of 1%. Based on the results of the study, it can be concluded that the Parigi Moutong government's promotional strategy, namely the Sail Tomini festival, which in this activity displays the natural charm and cultural tourism of Parigi Moutong with the help of Instagram and Facebook social media, is a very effective promotional tool in attracting visitors by the manager. The form of service the government provides to the community is to provide a forum for the community, such as providing training and outreach on developing tourist destinations. The opportunity for new jobs with this tourist destination is evident; all the employees who manage and are employed at the resorts are all residents of the Tandaigi village. And the existing facilities and infrastructure in the resort area of Tandagi Village have increased yearly, in addition to excellent primary road access. The existence of diving sports tourism in the Tamanigi village is in a suitable category.